2010
DOI: 10.1055/s-0029-1241826
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin Analogs on the Decline of Hemoglobin in Diabetic Patients with Nephropathy

Abstract: Insulin analogs mitigate the decline of hemoglobin in diabetic patients with impaired renal function. This might be due to a stimulating effect of insulin analogs on erythropoiesis via IGF receptor or a sustained activation of the insulin receptor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…Patients with normal kidney function also showed slightly higher hemoglobin values with glargine/lispro administration than with HI, and the difference bordered on statistical significance. These results confirm overall the findings of our earlier study in a smaller patient collective and extend them by the identification of two IAs that are essentially responsible for the hemoglobin-stabilizing effect [Hasslacher et al 2010].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Patients with normal kidney function also showed slightly higher hemoglobin values with glargine/lispro administration than with HI, and the difference bordered on statistical significance. These results confirm overall the findings of our earlier study in a smaller patient collective and extend them by the identification of two IAs that are essentially responsible for the hemoglobin-stabilizing effect [Hasslacher et al 2010].…”
Section: Discussionsupporting
confidence: 91%
“…Despite its clinical relevance, the relationship between the type of insulin therapy and the onset of diabetic complications has been poorly investigated. In a previous study, we reported IA to be associated with a better kidney function and smaller decrease in hemoglobin concentrations with declining kidney function than HI [Hasslacher et al 2010]. Due to the small number of patients, differentiation considering types of IAs was not possible in this early publication.…”
Section: Introductionmentioning
confidence: 99%